2016
DOI: 10.1093/mnras/stw2761
|View full text |Cite
|
Sign up to set email alerts
|

The mid-infrared polarization of the Herbig Ae star WL 16: an interstellar origin?

Abstract: We present high-resolution (0. ′′ 4) mid-infrared (mid-IR) polarimetric images and spectra of WL 16, a Herbig Ae star at a distance of 125 pc. WL 16 is surrounded by a protoplanetary disk of ∼ 900 AU in diameter, making it one of the most extended Herbig Ae/Be disks as seen in the mid-IR. The star is behind, or embedded in, the ρ Ophiuchus molecular cloud, and obscured by 28 magnitudes of extinction at optical wavelengths by the foreground cloud. Mid-IR polarization of WL 16, mainly arises from aligned elongat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…We do note, however, that there is no distinct Stokes I spectral fingerprint coinciding with the 10.3 µm polarization. It is unlikely that the well-known silicate feature or one of its variants can account for this polarization, since the silicate absorptive polarization profiles are broad, spanning the entire 8-13 µm region (e.g., Henning & Stognienko 1993;Smith et al 2000;Zhang et al 2017) rather than relatively narrow and sharp as the feature we see here. Other possibilities, including nanoparticles with silicate (Tielens 2013) or metallic Fe compositions, e.g., hygrogenated iron nanoparticles (Bilalbegović et al 2017), might be worth investigating (Hoang & Lazarian 2016) if further observations confirm and gain insight into the feature.…”
Section: Marginally Detected 103 µM Polarization Featurementioning
confidence: 64%
“…We do note, however, that there is no distinct Stokes I spectral fingerprint coinciding with the 10.3 µm polarization. It is unlikely that the well-known silicate feature or one of its variants can account for this polarization, since the silicate absorptive polarization profiles are broad, spanning the entire 8-13 µm region (e.g., Henning & Stognienko 1993;Smith et al 2000;Zhang et al 2017) rather than relatively narrow and sharp as the feature we see here. Other possibilities, including nanoparticles with silicate (Tielens 2013) or metallic Fe compositions, e.g., hygrogenated iron nanoparticles (Bilalbegović et al 2017), might be worth investigating (Hoang & Lazarian 2016) if further observations confirm and gain insight into the feature.…”
Section: Marginally Detected 103 µM Polarization Featurementioning
confidence: 64%
“…This source is undetected in polarization with a 3σ upper limit of 1.8%. Previously, Zhang et al (2017) found polarization fractions of 1 − 3% from spectropolarimetry at 8.7 µm and 10.3 µm toward WL 16. The mid-infrared polar- ization angles were also fairly uniform at ∼ 27 − 30 • toward the inner 2 of the mid-infrared disk.…”
Section: A Individual Sourcesmentioning
confidence: 88%
“…The mid-infrared polar- ization angles were also fairly uniform at ∼ 27 − 30 • toward the inner 2 of the mid-infrared disk. Zhang et al (2017), however, attribute their mid-infrared polarization to absorption from the foreground cloud rather than emission from the disk. Their mid-infrared polarization position angles and fractions are consistent with optical and near-infrared polarization of background stars (Sato et al 1988;Goodman et al 1990;Beckford et al 2008) and the expectations that this source is behind the Oph E cloud.…”
Section: A Individual Sourcesmentioning
confidence: 96%
“…However, polarized emission is not produced by dichroic emission and absorption alone, but also by scattering of stellar radiation and the thermal re-emission radiation of the dust, known as "self-scattering" (Kataoka et al 2015). Spectropolarimetry can help to distinguish dichroic emission from absorption (Aitken et al 2004;Zhang et al 2017), while distinguishing scattering from dichroic emission and absorption is less straightforward (Yang et al 2016). Scattering is often neglected in the mid-IR.…”
Section: Introductionmentioning
confidence: 99%